(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the multifaceted contribution of the medieval Central Asian scholar Mahmud al-Zamakhshari (1075–1144) to the development of Arabic linguistics, grammar, lexicography, and Qurʼanic exegesis. Born in the village of Zamakhshar in the Khwarazm region, al-Zamakhshari rose to become one of the most celebrated philologists, grammarians, and theologians of the classical Islamic world, earning the honorific titles Jarullah (“Neighbor of God”), Fakhr al-Khwarizm (“Pride of Khwarazm”), and Ustadh al-Arab wa al-ʿajam (“Teacher of Arabs and non- Arabs”). The study provides a comprehensive analysis of his four principal linguistic works: Al-Mufassal fi sanʿat al-iʿrab, the most systematic Arabic grammar written after Sibawayhi’s Kitab; Al-Unmuzaj fi al-nahw, a concise pedagogical grammar derived from the Mufassal; Muqaddimat al-adab, a pioneering multilingual encyclopedic dictionary prepared for non-Arab learners; and Asas al-balagha, a landmark Arabic lexicon organized on the principle of semantic derivation. The article further addresses his exegetical works Al-Kashshaf and Nukat al-iʿrab, in which grammatical and rhetorical analysis are systematically applied to Qurʼanic interpretation. Drawing on classical biographical dictionaries, medieval Arabic chronicles, and modern scholarship in Arabic and Orientalist traditions, the article argues that al-Zamakhshari’s achievement was not merely the accumulation of grammatical knowledge but the integration of grammar, rhetoric, lexicography, and exegesis into a unified and rigorous intellectual system that fundamentally shaped the subsequent history of Arabic linguistic science.